A era negra do Vale: café, escravos e senhores em Piraí - Gandra, Daniel Nogueira (2016)
This study analyzes the inventories of five of the richest coffee producers in the county of Piraí, in the Paraíba River Valley, between 1839 and 1848, summing almost two thousand slaves. In the economical bias, this study intends to demonstrate that the coffee economy produced enough surplus to allow its own expansion. The study also peruses the data about slave families in those inventories intending to demonstrate that slaves, who were mostly Africans, were active agents in the formation of their families, keeping a social life based on their memories and on the making of a new AfroBrazilian identity.